MENTORING AND EMPOWERING STUDENTS IN THE ACTUALIZATION OF CHILD-FRIENDLY BOARDING CURRICULUM BASED ON SYSTEMS THEORY AT THE BOARDING SCHOOL FOR CHILDREN OF INDONESIAN MIGRANT WORKERS - Zainal Arifin; Kholilur Rahman (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
The method used in this service is Asset Based Community Development (ABCD). Based on the results of the mentoring carried out at the An-Nahdloh Malaysia Islamic Boarding School, it can be concluded that improving the quality of students at the Islamic boarding school will not be successful if there is no cooperation and active participation from the mentoring subjects, associations and institutions that contribute actively to the An-Nahdloh Malaysia Islamic Boarding School and its students—donors who have contributed sincerely. The implementation of mentoring runs effectively and efficiently because it develops the quality of Santri HR assets in the knowledge and skills aspects of actualizing the PRA curriculum based on systems theory. In line with the implementation of the assistance carried out, it continues to increase the quality of curriculum development that will be implemented at the An-Nahdloh Malaysia Islamic Boarding School. The mentoring strategy that assists in actualizing the PRA curriculum is based on systems theory. Namely, it is carried out with a holistic, integrative strategy involving Islamic boarding school components, namely students, caregivers and administrators, in actualizing the PRA curriculum.